Hubungan Karakteristik dan Pengetahuan Ibu Hamil dengan Perilaku Hygiene Tentang Keputihan (Flour Albus) di Puskesmas Kalumpang Kota Ternate Tahun 2013 - Nuzliati T Djama; Amira BSA (Jurnal Kesehatan, 2014)
Abstract : Knowledge relations of pregnant women with the hygiene behavior about flour albus in Puskesmas Kalumpang Ternate Oktober 2013 Whiteness or Flour Albus is an abnormal vaginal secretion in women. Many women are not aware that they regard whitish vaginal discharge as common and trivial. Survey of health workers at the Puskesmas Kalumpang Ternate Incidence of Flour Albus / Whitish in pregnant women and pregnant women about the knowledge of flour albus / whiteness, from 100% of pregnant women around 55% of women do not know flour albus / discharge is physiological and pathological. The purpose of this study is to reveal Knowledge relations of pregnant women with the hygiene behavior about flour albus in Puskesmas Kalumpang Ternate Oktober 2013. The study design was descriptive correlational, design is cross sectional survey, with 30 samples of working mothers. The statistical analysis use in this study was bivariate.The results Relations knowledge of pregnant women with the hygiene behavior about flour albus in Puskesmas Kalumpang Ternate Oktober 2013, Based on the results showed a significant association (p = 0.036 ). Based on the Knowledge relations of pregnant women with the hygiene behavior about flour albus in Puskesmas Kalumpang Ternate Oktober 2013, can be considered in an effort to increase knowledge and awareness of the importance of maintaining the cleanliness of the area of sex organs.